Allergic diseases and pregnancy - A. V. Klemenov (Лечащий Врач)
Allergic reactions are quite common in pregnant women. The most common manifestations of an allergic reaction during pregnancy are: from the respiratory tract – allergic rhinitis and bronchial asthma, from the skin and subcutaneous tissue (allergodermatosis) – urticaria, angioedema, atopic dermatitis. As a rule, allergies do not affect the course of pregnancy, and pregnancy does not affect the allergic process, however, allergic reactions in pregnant women can cause difficulties associated with the selection of pharmaceuticals. The article discusses practical issues of pregnant women with allergic diseasesmanagement. Attention is paid to the place of non-drug methods: hypoallergenic diet and enterosorbents for food allergies, the use of sprays based on saline solutions for allergic rhinitis. Medication management of pregnant women suffering from allergic diseases is a compromise between the potential adverse effect of medications on the fetus and the course of pregnancy and the consequences of uncontrolled allergy. If it is necessary to prescribe antihistamines in the secondthird trimesters, it should be assumed that category B according to the FDA classification («no evidence of risk») includes chlorpheniramine, ciproheptadine (Peritol), diphenhydramine (Dimedrol), chlorotripelenamine (Suprastin), cetirizine (Zirtek, Cetrin), loratadine (Claritin), levocetirizine (Xizal). It is contraindicated to take astemizole, terfenadine, Tavegil (klemastin) because of the teratogenic or fetotoxic effect, desloratadine and ketotifen due to their ability to penetrate the placenta. Glucocorticosteroids are the drugs of choice in the treatment of severe forms of allergic diseases in pregnant women. Nasal corticosteroids are widely used in the treatment of moderate and severe allergic rhinitis. Inhaled glucocorticosteroids occupy a central place as a basic means for bronchial asthma. The drug of choice is budesonide, which has the best safety profile and has the greatest evidence base. Topical glucocorticosteroids (Advantan, Locoid, Elokom) in the form of creams and ointments are widely used in atopic dermatitis in pregnant women. If it is necessary to prescribe oral glucocorticosteroids (generalized urticaria, angioedema, severe exacerbation of atopic dermatitis), prednisone is preferred. Deposited glucocorticosteroids are categorically contraindicated. The use of cromoglycic acid, monoclonal antibodies, decongestants, bronchodilators is also discussed.